Spectrum optimization for computed radiography mammography systems. Issue 8 (August 2016) - Figl, Michael; Homolka, Peter; Semturs, Friedrich; Kaar, Marcus; Hummel, Johann
Highlights: A contrast-to-noise based spectrum optimization for CR mammo systems is presented. This is the first systematic study that put major emphases on CR systems. The results give a distinct recommendation for optimum tube voltage. Optimization of tube voltage can result in considerable dose reduction. Abstract: Purpose: Technical quality assurance is a key issue in breast screening protocols. While full-field digital mammography systems produce excellent image quality at low dose, it appears difficult with computed radiography (CR) systems to fulfill the requirements for image quality, and to keep the dose below the limits. However, powder plate CR systems are still widely used, e.g., they represent ∼ 30% of the devices in the Austrian breast cancer screening program. For these systems the selection of an optimal spectrum is a key issue. Methods: We investigated different anode/filter (A/F) combinations over the clinical range of tube voltages. The figure-of-merit (FOM) to be optimized was squared signal-difference-to-noise ratio divided by glandular dose. Measurements were performed on a Siemens Mammomat 3000 with a Fuji Profect reader (SiFu) and on a GE Senograph DMR with a Carestream reader (GECa). Results: For 50 mm PMMA the maximum FOM was found with a Mo/Rh spectrum between 27 kVp and 29 kVp, while with 60 mm Mo/Rh at 28 kVp (GECa) and W/Rh 25 kVp (SiFu) were superior. For 70 mm PMMA the Rh/Rh spectrum had a peak at about 31 kVp (GECa). FOM increases from 10% to >100% are demonstrated. Conclusion: Optimization as proposed in this paper can either lead to dose reduction with comparable image quality or image quality improvement if necessary. For systems with limited A/F combinations the choice of tube voltage is of considerable importance. In this work, optimization of AEC parameters such as anode-filter combination and tube potential was demonstrated for mammographic CR systems.